INOVASI DAN KREATIFITAS UMKM DI MASA PANDEMI (STUDI KASUS DI KABUPATEN BEKASI) - Reny Tri Juni Munthe; Dedi Rianto Rahadi (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
Currently the world is experiencing a Covid-19 pandemic, including in Indonesia. Therefore, an appeal to prevent the spread of the virus requires the public to remain silent. It is undeniable that all efforts have an impact and economic instability, one of which is MSMEs in Bekasi Regency. MSMEs are also part of the economy that must have the advantage to increase their innovation. The advantages in the current economy are innovation and creativity. For this reason, it takes the advantage of a creativity-based innovation that can make MSMEs in Bekasi Regency continue to survive and develop during the Covid-19 pandemic with a longer endurance and long term. This study uses a literature study method, the data obtained are compiled, analyzed with a descriptive approach so that we get conclusions from the literature study. In this study, taking literature data from several sources, namely library research, with data collection techniques by examining books, literature, theories, articles and notes on the internet according to related problems. The results of this study indicate that the existence of this innovation also requires motivation and creativity in a person so that they can achieve a goal and what forms of innovation and creativity can be done to MSMEs during this pandemic which will help open the minds of MSME actors, especially in Bekasi Regency to do or form a change in the future in order to continue to survive.